Adaptation of International Marriages in Mining Areas - Ashmarita; Rivai, Nening Febriana; Jers, La Ode Topo; Hartini; Genggong, Marsia Sumule (CV. Literasi Indonesia, 2024)
Mining companies play a vital role in driving economic growth, reducing unemployment, and creating business opportunities. Additionally, mines facilitate social and cultural interactions between local residents and foreign workers, with many of the latter eventually marrying locals in the vicinity. This study focuses on understanding the factors that influence the adaptation process of foreign workers with local residents in the Morosi District, Konawe Regency. It employs qualitative methods such as ethnographic research, involving direct observation and in-depth interviews. Data analysis is conducted using John W. Bennet's adaptation process theory. The research reveals that the adaptation of marriages between foreign workers and local residents is influenced by marriage agreements, which impact the support from partners and the acceptance of the relationship by families for the long term. If their work contracts in Morosi have ended, the couples agree to settle in Cina.